Simulation and optimization of coupling reaction of methanol synthesis and isopropyl alcohol dehydrogenation - Jenny Rizkiana; Yogi Wibisono Budhi; Azis Trianto (Jurnal Teknik Kimia Indonesia, 2011)
A study on simulation and optimization of coupling reaction between methanol synthesis and isopropyl alcohol (IPA) dehydrogenation was performed. The analysis is carried out theoretically to obtain the optimum operation conditions which give the best performance. The reactions are just interacting thermally. In this study, both reactions are held catalytically in a heat-exchanger type reactor. As a high pressure reaction, methanol synthesis is placed in the inner side of reactor tube while dehydrogenation of IPA is in the opposite. Tube wall acts as a heat transfer media. The reactor is modeled by a steady state heterogeneous equation for a fixed bed reactor. Optimization is done in order to find the optimum value of operation conditions, those are the inlet temperature of both side of reactor and the molar feed flow ratio between the exothermic side and the endothermic side. Sum of weighted reaction conversion is considered to be the objective function that is maximized. The simulation result shows that coupled reactor makes the reaction conversion higher than a conventional adiabatic reactor and the optimum operation conditions give the maximum value of the conversion. This study presents a theoretical proof that coupling reaction is feasible. Keywords: coupling reaction, IPA dehydrogenation, methanol synthesis, optimization, simulated annealingAbstrak Telaah mengenai simulasi dan optimisasi reaksi perangkaian (coupling reaction) antara sintesis metanol dengan dehidrogenasi isopropil alkohol (IPA) telah dilakukan. Analisis dilaksanakan secara teoretik guna mendapatkan kondisi optimum yang akan memberikan hasil terbaik. Pada penelitian ini, kedua reaksi dilaksanakan secara katalitik dalam reaktor bertipe buluh-cangkang. Karena bertekanan tinggi, sintesis metanol ditempatkan pada sisi buluh, sedangkan dehidrogenasi IPA ditempatkan pada sisi cangkang. Dinding buluh berperan sebagai media perpindahan panas. Reaktor dimodelkan dengan reaktor heterogen tunak unggun tetap. Optimisasi dilakukan dalam rangka mendapatkan nilai optimum dari kondisi operasi yang mencakup temperatur inlet sisi eksotermik dan endotermik serta rasio umpan molarnya. Jumlah total konversi reaksi terbobotkan dipilih sebagai nilai objectif yang akan dioptimumkan. Hasil simulasi menunjukkan bahwa reaktor perangkaian termal mampu meningkatkan konversi reaksi jika dibandingkan dengan reaktor adiabatik dan pada kondisi operasi yang optimum diperoleh konversi maksimal. Penelitian ini menunjukkan bahwa reaksi perangkaian layak untuk dilaksanakan.Kata kunci: reaksi perangkaian, dehidrogenasi IPA, sintesis methanol, optimisasi, simulated annealing